The Influence of Budget and Financial Control in Selected Government Parastatals in Nigeria - Ezekiel, AJAYI Ibidolapo; Obafemi, DADA Samuel (Journal of Contemporary Research in Social Sciences, 2021)
The study examined budget and financial control in selected government parastatals in Nigeria. The survey research design was adopted in the study. Primary data was obtained using a well-designed questionnaire. Data gathered in the study was analyzed using descriptive, correlation analysis, logit regression analysis and other post estimation tests. Findings obtained in the study indicated that budget preparation exerts insignificant positive impact on financial control in Nigerian government parastatals with coefficient estimate of .034178 (p=0.195> 0.05); budget implementation exerts insignificant positive impact on financial control of Nigerian government parastatals with coefficient estimate of .0082354 (p=0.750> 0.05) and budget monitoring and evacuation exert insignificant positive impact on financial control, with coefficient estimate of .0468773 (p=0.234> 0.05). Premise on these findings, the study concluded that financial control on the average tends to increase as government parastatals experience effectual budget performance, with more budget preparation, implementation and monitoring and evaluation as opposed to the usual neglect of budget after implementation. Hence, it was suggested that government should ensure improvement in budget design; government should ensure adequate budget monitoring procedure and government should ensure viable budget evaluation procedure.